Double emulsion (W/O/W) gel stabilised by polyglycerol polyricinoleate and calcium caseinate as mangiferin carrier: insights on formulation and stability properties. (31st May 2022) - Xing, Yuhang; Li, Ruyi; Xue, Lu; Chen, Mianhong; Lu, Xuli; Duan, Zhihao; Zhou, Wei; Li, Jihua
Summary: Mangiferin (MGF) is a phenolic compound isolated from mango, but its poor solubility significantly limits its use. In this study, MGF was embedded into the inner aqueous phase of W1 /O/W2 emulsions. Firstly, the dissolution method of MGF was determined. MGF remained stable in solution with pH 13 at 30 min, and its solubility reached 10 mg mL −1 . When the pH of MGF solutions was adjusted from pH 13 to pH 6, MGF did not immediately crystallise, providing sufficient time to construct the MGF‐loaded W1 /O/W2 emulsions. Subsequently, the MGF‐loaded W1 /O/W2 emulsions were constructed using polyglycerol polyricinoleate (PGPR) and calcium caseinate (CAS). The formation and stability of the W1 /O/W2 emulsions were investigated. The MGF‐loaded W1 /O/W2 emulsions stabilised with 1% PGPR and 1% – 3% CAS exhibited a low viscosity, limited loading capacity, and poor stability. Conversely, the MGF‐loaded W1 /O/W2 emulsions stabilised by 3%PGPR–3%CAS exhibited optimal loading capacity (encapsulation efficiency = 95.31% and loading efficiency = 0.91%) and stability, which was attributed to the fact that high viscosity and gel state retarded the migration of inner aqueous phase. These results indicated that the W1 /O/W2 emulsions stabilised by PGPR and CAS may be a potential alternative for encapsulating mangiferin. Abstract : Graphical Abstract